Jing shi zhi xing : gao ji xiao zu zhi ru he da cheng chuang xin gui mo hua - Humble, Jez; Molesky, Joanne; O'Reilly, Barry (Business consultant) (GoTop Information, Inc., 2016)
Detailed summary in vernacular field.